(untitled) (International Journal of Physiotherapy, 2016)
Background: Chronic obstructive pulmonary disease is a progressive disease characterized by airflow limitation or obstruction that is either not reversible at all or only partially reversible. The purpose of the present study was to compare oxygen saturation, pulmonary function and quality of life in the sample population from hill and plain area. Methods: A survey study, total sample size was of 100 patients of COPD (age between 40-70years) in which 50 each from hill and plain area. To find out desired result Oxygen saturation with pulse oximeter, pulmonary function test with spirometer and HRQOL with the SF-36 questionnaire was assessed. Result: Analysis using independent t- test to evaluate the significance of difference between means of two quantitative variables. The cut off level of significance was set at α = 0.05. And it has been found that the influence of COPD in hill and plain on oxygen saturation and HRQOL was significant for physical component score (4.08). There was minor and not significant for pulmonary function (1.77). Conclusion: From the results we concluded that COPD patients residing at hill has greater decline in SpO2 but the HRQOL in COPD patients residing at hill was better than patients residing at plain. There was little or no difference in pulmonary function by FEV1among COPD patients of hill and plain.